1977
DOI: 10.1152/ajpendo.1977.232.1.e85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin treatment on intestinal transport in the rabbit.

Abstract: The hormone serotonin (5-hydroxytryptamine) has been implicated as the cause of the diarrhea seen in many patients with the carcinoid syndrome. To determine whether serotonin is an intestinal secretagogue, the effect of serotonin on intestinal water and electrolyte transport was evaluated in the rabbit. Two weeks of daily subcutaneous injection of serotonin suspended in oil resulted in a blood serotonin level elevated to twice that of controls. Intestinal transport was studied in vivo by a perfusion technique.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…Previous studies have shown that 5-HT administration in vivo induces Cl Ϫ secretion in the rabbit small intestine (31) and acts as a mediator of diarrhea in patients with carcinoid syndrome associated with a net secretion of water and electrolytes (32). Therefore, these studies suggest an important role of 5-HT in modifying electrolyte transport process that could involve either stimulation of Cl Ϫ secretion or a decrease in Na ϩ and Cl -absorption.…”
Section: -Htmentioning
confidence: 71%
“…Previous studies have shown that 5-HT administration in vivo induces Cl Ϫ secretion in the rabbit small intestine (31) and acts as a mediator of diarrhea in patients with carcinoid syndrome associated with a net secretion of water and electrolytes (32). Therefore, these studies suggest an important role of 5-HT in modifying electrolyte transport process that could involve either stimulation of Cl Ϫ secretion or a decrease in Na ϩ and Cl -absorption.…”
Section: -Htmentioning
confidence: 71%
“…There is already substantial evidence that 5-HT affects transepithelial ion transport in the gut of a number of species including the rat (Hardcastle et al, 1981;Zimmerman & Binder, 1984), rabbit (Donowitz et al, 1977) and guinea-pig (Cooke & Carey, 1985). Some have considered that 5-HT acts directly on the enterocytes (Zimmerman & Binder, 1984) yet radioligand binding studies failed to show binding sites on the epithelial cells although they were present in the lamina propria (Gaginella et al, 1983;Gershon et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a well known fact that serotonin causes net water and electrolyte secretion in the small intestine in vivo (Donowitz et al, 1977;McFadden et al, 1986) and in vitro (Donowitz ef al., 1980a).…”
Section: Serotonin (5-hydroxytryptamine) (5 Ht)mentioning
confidence: 99%